Rasch model: a systematic review of Islamic instruments - Abu Bakar, Kaseh; Hassan, Siti Aishah; Hanafi, Norshafizah; Hayat, Bahrul; Badrasawi, Kamal Jamil (Universiti Sultan Azlan Shah, 2025)
Rasch model has gained prominence in validating psychometric instruments due to its robustness in measuring latent traits, ensuring validity and reliability across diverse populations. However, a systematic review of its evaluation of Islamic instruments has been lacking due to previously limited Islamic empirical studies. This review aims to assess the Rasch model in evaluating the psychometric properties of Islamic instruments. A thorough search via Scopus and Google Scholar, applying inclusion and exclusion criteria, documented 20 articles published between 2014 and 2024. The review highlights instruments assessing constructs based on Islamic and traditional values related to mental health literacy, religious conservatism, educational motivation, and well-being. Differential item functioning (DIF) was found in traditional beliefs, significantly affecting mental health literacy, religious conservatism, and motivation. Analysis showed several Islamic instruments had high item reliability but low person reliability. The necessity for rigorous Islamic instruments was emphasized by the observation of methodological difficulties, including sample representation and inclusions of Islamic core principles. The review highlights the Rasch model's effectiveness in developing reliable, valid, and culturally relevant measures, promoting holistic assessments in educational, psychological, financial, and religious studies. Future research should address these challenges to enhance the psychometric and methodological rigor of Islamic instruments.